Analysis of Onslag's Verdict Against Perpetrators of Gender Identity Forgery - Afwan Luthfi Nathoras Pohan; Imam Yazid (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2026)
Changing gender identity in population documents raises legal problems when associated with the alleged crime of forgery of letters as stipulated in Article 263 of the Criminal Code. This problem can be seen in the South Jakarta District Court Decision Number 583/Pid.B/2010/PN. Jkt.Sel jo. Decision of the Supreme Court of the Republic of Indonesia Number 704 K/Pid/2011 which confronts the interests of state administrative certainty with the principle of criminal responsibility. This study aims to analyze the construction of criminal liability for gender identity change and examine its conformity with Islamic criminal law principles. This research uses normative legal research methods with a legislative approach, a case approach, a conceptual approach, and a comparative approach. Legal materials are analyzed in a qualitative juridical manner through the study of court decisions, laws and regulations, criminal law doctrine, and jinyayah fiqh literature. The results of the study show that the difference in considerations between the District Court and the Supreme Court lies in the assessment of the elements of error (mens rea) and unlawful nature. The Supreme Court considered that identity changes carried out through legal procedures and supported by medical reasons did not meet the element of forgery because there was no intention to deceive or the purpose of obtaining unlawful profits. From the perspective of Islamic criminal law, this condition is in accordance with the concepts of tadlīs, 'udzur, and the principles of maqashid al-shari'ah which place intention and benefit as the basis for accountability. This study recommends the need for clearer regulation of gender identity change in order to create legal certainty and prevent criminalization of legitimate administrative actions.